PEMBUATAN SISTEM INFORMASI KOIN BOND DI PT SAGARA ASIA TECHNOLOGY MENGGUNAKAN SWIFT 4: Production of Koin Bond Information System at PT Sagara Asia Technology Using Swift 4 - Helmi Taufiq Al Hakim; Galih Suryo; Sofiyanti Indriasari (IPB University, 2021)
ABSTRACTPT Sagara Asia Technology or better known as Sagara Technology is a company engaged in technology consulting and digital products. Sagara Technology manufactures and provides premium software development, training and talent products. The work done at Sagara Technology focuses on developing website technology and mobile applications. Investment is an option for many groups of people to invest in a company because investment promises long-term benefits. Therefore, PT Lunaria Annua Teknologi decided to create a Bond Coin application to reach all groups of people who want to invest and can take advantage of investment returns according to their wishes.The methodology used during the creation of this application is Scrum. Scrum is used as a framework because this methodology is suitable for small teams, clear application specifications and Scrum allows iteration and incremental of a product requirement that will be found during product development. Bond coins make it easier for investors to conduct checks on Government Securities purchased, including transparency, security and efficiency in transactions.